Sequence Analysis and Preliminary X-ray Crystallographic Analysis of an Acetylesterase (LgEstI) from Lactococcus garvieae - Do, Hackwon; Wang, Ying; Lee, Chang Woo; Yoo, Wanki; Jeon, Sangeun; Hwang, Jisub; Lee, Min Ju; Kim, Kyeong Kyu; Kim, Han-Woo; Lee, Jun Hyuck; Kim, T. Doohun (Crystals (Basel), 2022)
A gene encoding LgEstI was cloned from a bacterial fish pathogen, Lactococcus garvieae. Sequence and bioinformatic analysis revealed that LgEstI is close to the acetyl esterase family and had maximum similarity to a hydrolase (UniProt: Q5UQ83) from Acanthamoeba polyphaga mimivirus (APMV). Here, we present the results of LgEstI overexpression and purification, and its preliminary X-ray crystallographic analysis. The wild-type LgEstI protein was overexpressed in Escherichia coli, and its enzymatic activity was tested using p-nitrophenyl of varying lengths. LgEstI protein exhibited higher esterase activity toward p-nitrophenyl acetate. To better understand the mechanism underlying LgEstI activity and subject it to protein engineering, we determined the high-resolution crystal structure of LgEstI. First, the wild-type LgEstI protein was crystallized in 0.1 M Tris-HCl buffer (pH 7.1), 0.2 M calcium acetate hydrate, and 19% (w/v) PEG 3000, and the native X-ray diffraction dataset was collected up to 2.0 Å resolution. The crystal structure was successfully determined using a molecular replacement method, and structure refinement and model building are underway. The upcoming complete structural information of LgEstI may elucidate the substrate-binding mechanism and provide novel strategies for subjecting LgEstI to protein engineering.